Effects of Trade Openness and Foreign Direct Investment (FDI) Inflows on Unemployment in West African Economic and Monetary Union (WAEMU) Member Countries - Behanzin, Tomondji Dayane Thiernaud; Konte, Mamadou Abdoulaye (DEMO, 2022)
The objective of this paper was to measure the effect of trade openness and foreign direct investment inflows (FDI) on unemployment in WAEMU countries. To do so, the Vector Autoregressive (VAR) model in panel was used. The results show that there is a bidirectional causality between FDI and trade openness, FDI and unemployment, and a unidirectional causality of unemployment on trade openness. Furthermore, the robust results show that FDI inflows reduce unemployment and thus promote job creation in WAEMU member countries. In addition, the analysis shows that trade openness and FDI inflows increase youth employment (15-24 years old) and encourage migration from vulnerable jobs to less vulnerable jobs.(original abstract)